"What activism can learn from poetry": Lyric Opacity and Drone Warfare in Solmaz Sharif’s LOOK - Finberg, Keegan Cook (Review of International American Studies, 2022)
The essay explores whether concealing humanness or emphasizing humanness is a more effective strategy for anti-drone activism that seeks to disrupt the conventional epistemologies of militarized surveillance. Building on Édouard Glissant’s decolonizing philosophy of relation and more recent theories of gender and surveillance such as Rachel Hall’s notion of “animal opacity,” the essay argues that poetry is one place we might find an answer to what seems like a binary problem of seeing versus unseeing humanity in technologically mediated aerial warfare. I illustrate that the 2016 poetry collection LOOK by Solmaz Sharif intervenes to suggest activism that steers readers away from the logics of recognition and toward the ethical potential of concealment. LOOK garners formal elements from lyric and experimental poetry traditions to employ a strategy of resistance-looking based in multiple valences of opacity.multiple valences of opacity.